LITERATURE REVIEW: RELATIONSHIP BETWEEN ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) ON FINANCIAL PERFORMANCE (FP) - Rinda Fithriyana; Fajri Adrianto; Rida Rahim (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This literature review article discusses the relationship between environmental, social and corporate governance (ESG) on the company's financial performance. By using a systematic literature review method, this article tries to collect various research results on ESG-FP. By using the main theory of stakeholders and agency theory.